Jazz Specifics and the Characterization and Structure of El invierno en Lisboa. - Franz, Thomas R. (Revista de Estudios Hispánicos)
The article discusses references to jazz music and musicians in the novel "El invierno en Lisboa," by Spanish writer Antonio Muñoz Molina. Artists such as Louis Armstrong, pianist Jellyroll Morton, and Thelonius Monk are all mentioned in the novel. While the book takes place during the 1960s when the jazz greats of the 1940s and 1950s were in decline, the book does not produce an image of jazz from a specific point in time. The article examines how these brief references to jazz music shape the novel's narrative.